Michel Foucault en die historisering van Anderswees - Beukes, Johann C. (Hervormde teologiese studies, 1996)
Michel Foucault and the historization of Otherness In this article the intimate relation between power, history and historiography is explored within the context of the postmodem philosophy/ historiography of Michel Foucault. Foucault confronts us with a timeless question: do we recognize our own dicourses of power? Do we recognize the Other, the victims of instrumental reason? At the end of the Middle Ages leprosy disappeared from the face of the earth.(Michel Foucault: Opening sentence in Madness and Civilization)